A CdSe thin film: a versatile buffer layer for improving the performance of TiO2 nanorod array:PbS quantum dot solar cells. Issue 19 (28th April 2016) - Tan, Furui; Wang, Zhijie; Qu, Shengchun; Cao, Dawei; Liu, Kong; Jiang, Qiwei; Yang, Ying; Pang, Shan; Zhang, Weifeng; Lei, Yong; Wang, Zhanguo
Abstract : A CdSe buffer layer was used for PbS quantum dot:TiO2 nanoarray solar cells. The efficiency is among the best ones. Abstract : To fully utilize the multiple exciton generation effects in quantum dots and improve the overall efficiency of the corresponding photovoltaic devices, nanostructuralizing the electron conducting layer turns out to be a feasible strategy. Herein, PbS quantum dot solar cells were fabricated on the basis of morphologically optimized TiO2 nanorod arrays. By inserting a thin layer of CdSe quantum dots into the interface of TiO2 and PbS, a dramatic enhancement in the power conversion efficiency from 4.2% to 5.2% was realized and the resulting efficiency is one of the highest values for quantum dot solar cells based on nanostructuralized buffer layers. The constructed double heterojunction with a cascade type-II energy level alignment is beneficial for promoting photogenerated charge separation and reducing charge recombination, thereby responsible for the performance improvement, as revealed by steady-state analyses as well as ultra-fast photoluminescence and photovoltage decays. Thus this paper provides a good buffer layer to the community of quantum dot solar cells.